Epidermoid Cyst Localized in Bilateral Palatine Tonsils – A Rare Case Report - Mistry, Krishna Vijaykumar; Kahar, Manoj A (Annals of Pathology and Laboratory Medicine, 2024)
Epidermoid cysts (ECs) are benign lesions that can occur throughout the body, but they have a low incidence in the head and neck region (1.6 to 7%). In the oral cavity, the most commonly affected site is the floor of the mouth, while tonsillar location remains extremely rare (less than 0.01%). Here, we present a case of bilateral epidermoid cysts of the palatine tonsils, which were incidentally detected in a patient.